A Comparison of NOTES Transvaginal and Laparoscopic Cholecystectomy Procedures Based upon Task Analysis - Nemani, Arun (2014)
BACKGROUND: A virtual reality-based simulator for Natural Orifice Translumenal Endoscopic Surgery (NOTES) procedures may be used for training and discovery of new tools and procedures. Our previous study [19] shows that developing such a simulator for the transvaginal cholecystectomy procedure using a rigid endoscope will have the most impact on the field. However, prior to developing such a simulator, a thorough task analysis is necessary to determine the most important phases, tasks, and subtasks of this procedure. METHODS: 19 rigid-endoscope transvaginal hybrid NOTES cholecystectomy procedures and 11 traditional laparoscopic procedures have been recorded and de-identified prior to analysis. Hierarchical task analysis (HTA) was conducted for the rigid-endoscope transvaginal NOTES cholecystectomy. A time series analysis was conducted to evaluate the performance of the transvaginal NOTES and laparoscopic cholecystectomy procedures. Finally, a comparison of electrosurgery based errors was performed by two independent qualified personnel. RESULTS: The most time consuming tasks for both laparoscopic and NOTES cholecystectomy are removing areolar and connective tissue surrounding the gallbladder, exposing Calot’s triangle, and dissecting the gallbladder off the liver bed with electrosurgery. There is a positive correlation of performance time between the removal of areolar and connective tissue and electrosurgery dissection tasks in NOTES (r = 0.415) and laparoscopic cholecystectomy (r = 0.684) with p < 0.10. During the electrosurgery task, the NOTES procedures had fewer errors related to lack of progress in gallbladder removal. Contrarily, laparoscopic procedures had fewer errors due to the instrument being out of the camera view. CONCLUSION: A thorough task analysis and video-based quantification of NOTES cholecystectomy has identified the most time consuming tasks. A comparison of the surgical errors during electrosurgery gallbladder dissection establishes that the NOTES procedure, while still new is not inferior to the established laparoscopic procedure.